Optimal dynamic path during the transition of exchange rate regime: Analysis of the People's Republic of China (PRC), Malaysia, and Singapore - Naoyuki Yoshino; Tamon Asonuma (Asian Development Bank Institute (ADBI), 2017)
This paper considers the optimal exchange rate regime transition policy for three East Asian countries: the People's Republic of China (PRC), Malaysia, and Singapore. In contrast to two traditional approaches to exchange rate regimes in East Asia, the paper conducts a dynamic transition analysis. Based on a small, open-economy dynamic stochastic general equilibrium model applied to these three countries, we define transition policies from a dollar peg regime to either a basket peg or a floating regime and compare the welfare gains of these policies relative to maintaining the current dollar peg regime. The quantitative analysis using PRC, Malaysian, and Singaporean data shows that the PRC would be better off shifting gradually from a dollar peg to a basket peg. In response to the PRC's shift, both Malaysia and Singapore would opt to shift gradually to a basket peg regime.
Keywords: F33; F41; F42; 330; Economics; China; People's Republic of; Malaysia; Singapore